The Differences and the Intersections of Literary Criticism - Hartmanová, Pavla (Bohemica Olomucensia, 2023)
This article aims to present the results of a quantitative analysis of bibliographical data about the Czech literary criticism in 2021. The source of these data is the Czech literary bibliography article database. The database contains information not only about print periodicals but also about online sources. For this reason, the article compares results from these two areas. The analysis shows differences and similarities between print and online criticism - which books or writers were evaluated and who created literary discourse. The literary criticism is examined from the point of view of gender and age of critics too. The article brings new information mainly about online literary criticism, which has not recieved much attention yet. Base on analysed data was indicated whether exists a correlation between awarded books and literary reflection in media.
Keywords: literary criticism; critics; print sources; electronic sources; awarded books; bibliograhical data; Czech Literary Bibliography